The Ability to Write Procedural Text Through Titiz Craft YouTube Channel - Humairah, Nurul (STKIP Agama Hindu Singaraja, 2024)
This research was driven by the reduced learning ability and interest of students in learning to write procedural texts. This research is a qualitative descriptive research. The aim of this research is to describe the learning steps, writing skills using the Titiz Craft YouTube Channel, and the obstacles experienced in the learning text procedures for class XI students at SMA Negeri 1 Woha. The data collection techniques used in this research were observation, interviews and documentation. The results of this research show that the learning process at SMA Negeri 1 Woha is carried out face-to-face and the Titiz Craft YouTube Channel has been implemented as a learning medium. Students' abilities in text learning procedures via the Titiz Craft YouTube Channel were said to be successful with an average score of 80. One of the obstacles that faced students during learning was that students had difficulty using standard language and vocabulary.